Implementation of Biological Learning Management to Produce Productive Teachers - Akhmad Akhmad (PT ARRUS Intelektual Indonesia, 2024)
The implementation of learning management plays a very decisive role in the teaching and learning process. The biology teaching and learning process is the core of the formal education process, with the teacher as the main actor. This research uses the field study method (Field Research). Sources of data in this study using the purposive sampling technique. The data collected are data collection (field notes), data reduction (data reduction), data display (data presentation), and conclusion drawing/verification. The results of this study are teachers are very skilled in prioritizing the ability to open lessons, prioritizing Mastery of learning materials, referring to planned teaching and learning activities, and prioritizing the ability to use learning media. The implementation of biology learning management in this study includes four main functions in education management: planning, organizing, acting, and evaluating. Thus, good school management certainly produces school principals with good educational management implementation and has productive teachers in the teaching process in schools.